Upah Buruh dalam Perspektif Islam - Rizqa Amelia; Nadya Maulidya Manurung; Mustafaruddin Mustafaruddin (FEB Universitas Maritim Semarang, 2023)
The research objective is to understand or observe how labor wages are according to several hadith economic theories. The descriptive study of the writing methodology used in this publication uses a qualitative approach with the aim of providing a clear overall picture of an event. The data collection method used was a literature review. Part of the literature review is research processing, reading and taking notes, and using data collection techniques. Reliable sources, journals, articles and other sources. These data include secondary data from various books, depending on the type. Due to differences in talent and ability, Islamic economics recognizes that wages are paid by those who cause material results to vary. Due to the difference in talent and ability, Islamic economics recognizes that wages are paid by, which causes different material results. Theoretically, wages are the prime mover of human labour